PSYCHOLOGICAL OWNERSHIP PERSPECTIVE: STRENGTHENING EMPLOYEE ENGAGEMENT BY SELF-EFFICACY, JOB CHARACTERISTICS, THROUGH JOB SATISFACTION - noor arifin, noor arifin (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This research aims to examine the influence of self-efficacy and job characteristics on employee engagement, with job satisfaction serving as a mediating variable among CV. Kalingga Jaya employees. A quantitative approach was employed using a survey method, distributing questionnaires to 116 participants, and the data were analyzed with the Partial Least Square (PLS) technique. The findings reveal that both self-efficacy and job characteristics significantly and positively impact employee engagement, directly as well as indirectly through job satisfaction. Employees with higher self-efficacy tend to have greater confidence, which enhances their job satisfaction and subsequently strengthens their engagement. Likewise, jobs that are perceived as meaningful and interesting increase satisfaction and further reinforce engagement. These results highlight that efforts to foster employee engagement should prioritize developing employees’ self-efficacy, improving job design quality, and creating a work environment that promotes satisfaction. Theoretically, this study contributes to enriching the framework linking personal resources, job characteristics, job satisfaction, and employee engagement. Psychological ownership theory suggests that individuals demonstrate stronger commitment, care, and proactive behavior when they feel personally invested. Therefore, employee engagement becomes stronger when individuals believe in their own abilities (self-efficacy), find meaning in their work (job characteristics), and feel content with their jobs (job satisfaction) within an industrial context.